1999
DOI: 10.1200/jco.1999.17.7.2050
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Endometrial Abnormalities in Asymptomatic Women Treated With Tamoxifen and an Evaluation of the Role of Endometrial Screening

Abstract: TV USS detects a high incidence (41%) of apparent endometrial thickening in women treated with tamoxifen, although 46% had atrophic endometrium on further assessment, and none of the remaining asymptomatic women had significant lesions. Length of time on tamoxifen relates to endometrial thickening as measured by TV USS. TV USS is a poor screening tool because of the high false-positive rate. The low frequency of significant findings suggests that endometrial screening in asymptomatic women is not worthwhile.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
1
8

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(89 citation statements)
references
References 24 publications
6
74
1
8
Order By: Relevance
“…However, in studies that have evaluated ultrasound screening for endometrial abnormalities in women receiving tamoxifen, approximately 21-41% of women proceed to endometrial sampling. [25][26][27] As a result of the high frequency of abnormalities and the low positive predictive value, there is near uniform consensus that routine transvaginal sonography or random endometrial biopsy is not indicated for women receiving tamoxifen. 28,29 Similar issues, however, are likely to be relevant in the setting of ovarian carcinoma screening in high-risk women as a substantial number will have a personal history of breast carcinoma and possible tamoxifen use (61% and 38%, respectively, in our cohort).…”
Section: Discussionmentioning
confidence: 99%
“…However, in studies that have evaluated ultrasound screening for endometrial abnormalities in women receiving tamoxifen, approximately 21-41% of women proceed to endometrial sampling. [25][26][27] As a result of the high frequency of abnormalities and the low positive predictive value, there is near uniform consensus that routine transvaginal sonography or random endometrial biopsy is not indicated for women receiving tamoxifen. 28,29 Similar issues, however, are likely to be relevant in the setting of ovarian carcinoma screening in high-risk women as a substantial number will have a personal history of breast carcinoma and possible tamoxifen use (61% and 38%, respectively, in our cohort).…”
Section: Discussionmentioning
confidence: 99%
“…Formerly there was controversy regarding the most appropriate approach to monitoring the endometrium in women using tamoxifen, with some investigators suggesting that routine endometrial sampling be performed on an annual basis. However, current evidence suggests that such an approach consumes resources without improving survival rates 39,40 (Class 3). Consequently, and at least for the present, only women receiving tamoxifen who experience uterine bleeding should be investigated.…”
Section: Endometrial Cancer and Tamoxifenmentioning
confidence: 99%
“…Uno de sus efectos adversos más destacable es su acción proliferativa sobre el endometrio, desde hiperplasias, pólipos, carcinomas y sarcomas; llegando a identificarse hasta en el 36% de los casos tratados 1 pero tratándose en su mayoría de alteraciones benignas del útero. Es por ello por lo que los ensayos prospectivos en este tipo de pacientes no desaconsejan el uso del tamoxifeno como tratamiento coadyuvante [2][3][4] , aunque se investigan otras líneas carentes de estos efectos adversos como los inhibidores de la aromatasa. Queremos presentar aquí 2 casos de sarcomas uterinos, en dos pacientes postmenopáusicas tratadas con tamoxifeno por un cáncer de mama, como una patología aunque poco frecuente, ampliamente descrita en la bibliografía.…”
Section: Introductionunclassified